Pengaruh Nilai Utama ASN Berakhlak dan Motivasi Kerja terhadap Kinerja Karyawan di Badan Kesatuan Bangsa dan Politik Kota Surabaya - Purwanti, Purwanti; Nugrohoseno, Dwiarko (Ridwan Institute, 2025)
This study aims to analyze the influence of the core values of ASN BerAKHLAK and work motivation on employee performance at the National Unity and Political Agency of Surabaya City. This research employs a quantitative approach with data analysis using multiple linear regression. The sample consists of 100 employees working at the agency, selected randomly. Data were collected through a questionnaire measuring the variables of ASN BerAKHLAK core values, work motivation, and employee performance. Statistical analysis was conducted using SPSS to test the hypotheses and examine the impact of these variables on employee performance. The results indicate that both the ASN BerAKHLAK core values and work motivation have a significant effect on employee performance. Specifically, the ASN BerAKHLAK core values play a crucial role in shaping a positive work culture, while work motivation enhances individual productivity and performance quality. These findings are expected to contribute to the development of policies related to employee performance management in government institutions, particularly in optimizing the implementation of ethical values and work motivation.